Medicinal polypharmacology—a scientific glossary of terminology and concepts - Stefan, Sven Marcel; Rafehi, Muhammad (Frontiers in Pharmacology, 2024)
Medicinal polypharmacology is one answer to the complex reality of multifactorial human diseases that are often unresponsive to single-targeted treatment. It is an admittance that intrinsic feedback mechanisms, cross-talk, and disease networks necessitate drugs with broad modes-of-action and multitarget affinities. Medicinal polypharmacology grew to an independent research field within the last two decades and stretches from basic drug development to clinical research. It has developed its very own terminology embedded in general terms of pharmaceutical drug discovery and development at the cross-road between medicinal chemistry, chemical biology, and clinical pharmacology. A clear and precise language of critical terms and a thorough understanding of underlying concepts is imperative; however, no comprehensive work exists to this date that could support researchers in this and adjacent research fields. In order to explore novel options, to establish interdisciplinary collaborations, and to generate high-quality research output, the present work provides a first-in-field glossary to clarify on the numerous terms that originated from various individual disciplines.